20-nm enhancement-mode metamorphic GaAs HEMT with highly doped InGaAs source/drain regions for high-frequency applications. Issue 3 (4th March 2017) - Ajayan, J.; Nirmal, D.
ABSTRACT: In this article, the DC and RF performance of a SiN passivated 20-nm gate length metamorphic high electron mobility transistor (MHEMT) on GaAs substrate with highly doped InGaAs source/drain (S/D) regions have investigated using the Synopsys TCAD tool. The 20-nm enhancement-mode (E-mode) MHEMT device also features δ-doped sheets on either side of the In0.53 Ga0.47 As/InAs/In0.53 Ga0.47 As channel which exhibits a transconductance of 3100 mS/mm, cut-off frequency (fT ) of 740 GHz and a maximum oscillation frequency (fmax ) of 1040 GHz. The threshold voltage of the device is found to be 0.07 V. The room temperature Hall mobilities of the 2-dimensional sheet charge density are measured to be over 12, 600 cm 2 /Vs with a sheet charge density larger than 3.6 × 10 12 cm −2 . These high-performance E-mode MHEMTs are attractive candidates for sub-millimetre wave applications such as high-resolution radars for space research, remote atmospheric sensing, imaging systems and also for low noise wide bandwidth amplifier for future communication systems.